2015
DOI: 10.1007/s10856-015-5489-0
|View full text |Cite
|
Sign up to set email alerts
|

Photocrosslinked layered gelatin-chitosan hydrogel with graded compositions for osteochondral defect repair

Abstract: A layered gelatin-chitosan hydrogel with graded composition was prepared via photocrosslinking to simulate the polysaccharide/collagen composition of the natural tissue and mimic the multi-layered gradient structure of the cartilage-bone interface tissue. Firstly, gelatin and carboxymethyl chitosan were reacted with glycidyl methacrylate (GMA) to obtain methacrylated gelatin (Gtn-GMA) and carboxymethyl chitosan (CS-GMA). Then, the mixed solutions of Gtn-GMA in different methacrylation degrees with CS-GMA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…24 There is another possibility of self-cross-linking of chitosan and gelatin chains. 40 Different concentrations of polymers were utilized in this study (data not shown). Among the different combinations of varying polymer concentrations, we found good mechanical stability using a 1% chitosan concentration with 1% gelatin and 2% or 3% agarose in the polymer solution mixture (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…24 There is another possibility of self-cross-linking of chitosan and gelatin chains. 40 Different concentrations of polymers were utilized in this study (data not shown). Among the different combinations of varying polymer concentrations, we found good mechanical stability using a 1% chitosan concentration with 1% gelatin and 2% or 3% agarose in the polymer solution mixture (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Estos pueden diseñarse para mimetizar aspectos fundamentales del ambiente nativo, para proveer de señales apropiadas a las células que se siembran en él, mientras se ajustan precisamente las propiedades mecánicas, químicas y degradadoras del hidrogel. [60][61][62][63][64] Por ejemplo, el porcentaje de hidratación también se puede regular para asemejarse al del cartílago nativo (~80%) y favorecer el intercambio celular de substratos, y productos peri-y extracelulares. 14 Las ventajas de los polímeros naturales son su biocompatibilidad, su similitud bioquímica con el cartílago nativo y su facilidad para ser degradados (p.…”
Section: Polímeros In Situ O Polímeros 3dunclassified
“…[9, 21, 22] Injectable hydrogel systems, which can be gelled in situ , are advantageous since their applications can be minimally invasive and directly delivered to the damage site. [9] Such injectable hydrogel systems include those based on poly(ethylene glycol),[2325] gelatin,[26, 27] chitosan,[27, 28] alginate,[29] chondroitin sulfate,[30] carboxymethylcellulose,[31] poly(vinyl alcohol),[32, 33] and HA. [3439] While implanted materials must be biocompatible and meet the mechanical needs of the tissue,[5, 8, 9] they must also integrate with the surrounding tissue, in this case forming a cartilage-hydrogel interface.…”
Section: Introductionmentioning
confidence: 99%